KASCHNITZ INTO ENGLISH : SIX SHORT STORIES AND ESSAYS - Bandy, Ann Monica (My University, 1994)
Marie Luise Kaschnitz continues to be almost unknown in North America despite her status in Germany as an important poet and writer. Writing through and after the worst years of modern German history, the political depravity of the thirties and forties and the physical devastation of t he war years and their aftermath, Kaschnitz told stories involving characters in various states of denial, isolation and alienation. Her characters are awakened by some cathartic event and then react to that awakening in different ways. In "The Sleepwalker" a woman made aware of the ugliness around herself throws herself before a truck. In "Life After Death" a near-death experience transforms two girls in opposite ways . A listening audience, in "The Violinist, " is unable, or refuses to hear the healing message in a musician's performance . The husband and wife, in "Polar Bears, " attempt to communicate across a gulf symbolized by his death. The essays "On the Nature of the ' l' " and "On Journeying Through the Depths" examine the effect of the Nazi regime on the German psyche and the best route to healing . Through these stories and essays we can see Kaschnitz's fascination with "das Unheimliche," myth, and her tendency to draw her stories from her own life experiences.
Translating Kaschnitz presents many challenges arising from her lyrical style of writing. Kaschnitz's writing does not only speak to the conscious mind but also seeks to reach the reader at an emotional and intuitive level. l have attempted to make consistent choices and have explained those choices in the two introductory essays referring. l have also illustrated the effects of such choices by discussing two translators of Kaschnitz who have differing approaches, Donald MacRae and Lisel Mueller. To add a critical perspective to the translations , l have prefaced each story or essay with a discussion of the themes present and the context in which it was written. The select i on of stories and essays have been arranged in chronological order to show the development of her writing style and thematic concerns.
Keywords: German Language and Literature; German Language and Literature